Association of serum leptin levels in patients with chronic periodontitis and cardiovascular diseases - Bhavya Indraganti; Yalamanchili Pallavi Samatha; Satya Kishore Chivukula; Hemchand Surapaneni; Challa Bharath Chandra; Rohith Atluri (Wolters Kluwer Medknow Publications, 2023)
Background: In recent years, clinical studies have shown an association between leptin and periodontal disease. The present study aimed to estimate and compare the serum leptin levels in chronic periodontitis patients with cardiovascular diseases. Materials and Methods: A total of 30 subjects were included in the study and are divided into three groups, i.e. Group 1: ten healthy subjects, Group 2: ten subjects with chronic periodontitis, and Group 3: ten subjects with periodontitis and cardiovascular disease. Two millimeters of the venous blood sample was collected from the antecubital fossa of all the sixty subjects under aseptic conditions. Serum was obtained from the blood by centrifuging at 2500 rpm for 10 min. Now, this collected serum is used to estimate leptin using a leptin enzyme-linked immunosorbent assay (ELISA) kit (Clementia biotech). Leptin levels were assessed in an ELISA reader. Statistical analysis was conducted using SPSS software version 24. Results: A significant correlation was observed with serum leptin levels and clinical parameters in the chronic periodontitis + cardiovascular disease group, i.e. plaque index (r = −0.96, P = 0.0003*), gingival index (r = −0.89; P = 0.0005*), probing depth (r = −0.82; P = 0.003*), and clinical attachment level (r = −0.84; P = 0.001*) * is Statistically Significant. Conclusion: The study found a statistically significant increase in serum leptin levels in the Group III compared to Groups II and I which suggest an increase in inflammatory state increases the serum levels of leptin.